Kajian Teori: Pandangan Vygotsky Dalam Pembelajaran Matematika Menggunakan Problem Posing Di Kurikulum Merdeka (Universitas Dr. Soetomo, 2024)
The mathematics learning approach involving Vygotsky's views and the application of the problem posing method in the context of the Independent Curriculum has attracted the attention of educational researchers. Vygotsky's views and Piaget's theory are constructivist, with a connecting line between the cognitive flow and the social approach, where constructivism has similarities with the social approach. This research aims to explore key concepts from Vygotsky's theory in mathematics learning, with a focus on the problem posing approach in the newly implemented curriculum. Descriptive methods are used to analyze Vygotsky's views in the context of solving mathematical problems using a problem posing approach. The main references in this research are articles published in international and national journals indexed at least SINTA 4. The results of this research are expected to provide deeper insight into how Vygotsky's concepts can be applied in creative and student-centered mathematics learning in Independent Curriculum Keywords: Vygotsky, problem posing, mathematics learning, independent curriculum Pendekatan pembelajaran matematika yang melibatkan pandangan Vygotsky dan penerapan metode problem posing dalam konteks Kurikulum Merdeka telah menarik perhatian para peneliti pendidikan. Pandangan Vygotsky dan Teori Piaget merupakan aliran kontruktivis, dengan garis penghubung aliran kognitif dan pendekatan sosial, dimana kontrukstivis memiliki kesamaan dengan pendekatan sosial. Penelitian ini bertujuan untuk mengeksplorasi konsep-konsep kunci dari teori Vygotsky dalam pembelajaran matematika, dengan fokus pada pendekatan problem posing dalam kurikulum yang baru diimplementasikan. Metode deskriptif digunakan untuk menganalisis pandangan Vygotsky dalam konteks pemecahan masalah matematika dengan pendekatan problem posing. Referensi utama dalam penelitian ini adalah artikel-artikel yang terpublikasi dalam jurnal internasioanl dan nasional yang terindeks minimal SINTA 4. Hasil penelitian ini diharapkan dapat memberikan wawasan yang lebih dalam tentang bagaimana konsep-konsep Vygotsky dapat diaplikasikan dalam pembelajaran matematika yang kreatif dan berpusat pada siswa pada Kurikulum Merdeka Kata Kunci: Vygotsky, problem posing, pembelajaran matematika , kurikulum merdeka